MECHANISMS OF TEACHER PROFESSIONAL ADVANCEMENT SYSTEM FORMATION - Makarova, L.N.; Gushchina, T.I. (Tambov University Review. Series: Humanities, 2016)
Taking into consideration strategic documents in the sphere of education the basic mechanisms of teacher professional advancement are worked out. The advantages of multi-level educational complex of Pedagogy institute of Tambov State University named after G.R. Derzhavin in the context of continuous system of professional advancement of teacher in modern social-economic conditions. The possibilities of every level of educational complex from the positions of their importance for further personal-professional advancement of a teacher: pre-professional preparation, secondary vocational education higher education (baccalaureate, master’s program), post-diploma education. All realized educational programs have variant nature, ready for changes, contain significant unit of the electives according to the needs of future teacher and are aimed at formation of work functions complex, pointed in professional standard of a teacher. Attention is paid to forms and methods of teaching, which provide professional advancement of modern teacher: andragogy methods, innovative-reflective practice (positional discussions, polylogue; method of projects, inversions, contrasts reflections), sandwich preparation, maximal use of creative tasks, developed on the basis of neuropedagogy positions. The growth of amount and variants of individual ways due to which you can start teacher’s profession and develop your professional skills, let create the system of constant professional development (professional advancement) from specialized form to the teacher’s career.